Algerian immigration to France during the French occupation period 1830-1962 AD - a reading of the causes and motives - - Samia BENFATIMA; Boubaker HAFDELLAH (Social Sciences Journal, 1970)
Since its occupation of Algeria in 1830, France has sought to make it dependent on it, It hasadopted a settlement policy aimed at eliminating the Algerian people completely. The Algerianeconomy is thus transformed from a subsistence farming economy to a monetary economy aimed atserving the French own economy. Thus, many economic, social and psychological causes are met tolead a number of Algerians to a sense of alienation within their homeland ruled by France. The lattertried hard to put the Algerians in a narrow space, deprived of their rights. Many Algerians choseforeign countries as a destination for emigration. So; the act of emigration was a form of resistanceagainst France, a resistance that expresses resentment and rejected an abhorrent occupier. Throughthis resistance, the Algerian emigrants demanded freedom and respect and may be opportunities thatare no longer provided by their usurped homeland